2013
DOI: 10.1016/j.diii.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Pure flat epithelial atypia: Is there a place for routine surgery?

Abstract: In patients with no personal or first-degree family history of breast cancer, after complete or subtotal excision under radiology of the radiological lesion, and while excluding images fitting BI-RADS 5, annual monitoring may be offered as an alternative to surgical excision in view of the absence of underestimation found in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
3
13
2
Order By: Relevance
“…An issue in the current clinical management of FEA is the question of surgical excision when FEA is diagnosed with core needle biopsy. Although outside the scope of the current investigation, other retrospective studies have reported that cancer is found in approximately 3% to 13% of women with FEA on core needle biopsy who subsequently undergo surgical excision . This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…An issue in the current clinical management of FEA is the question of surgical excision when FEA is diagnosed with core needle biopsy. Although outside the scope of the current investigation, other retrospective studies have reported that cancer is found in approximately 3% to 13% of women with FEA on core needle biopsy who subsequently undergo surgical excision . This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH.…”
Section: Discussionsupporting
confidence: 57%
“…This finding is not surprising, given the association between FEA and AH that we observed, and the known risk of an upgrade to cancer with surgical excision of AH. In addition to a small risk of detecting cancer at the time of surgical excision, multiple studies have reported finding other high‐risk lesions (AH or lobular carcinoma in situ) in 20% to 52% of women undergoing excision of FEA found at core needle biopsy . Although the majority of studies recommend surgical excision for FEA detected on core needle biopsy, others have suggested that this might not be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Management recommendations in corporate the actual risk of progression, which is low. Open biopsy must be considered when suspicious microcalcifica tions or a mass lesion remain radiologically detectable after core needle or vacuumassisted biopsy [37].…”
Section: Prognostic and Predictive Factorsmentioning
confidence: 99%
“…712 Nevertheless, a diagnosis of FEA includes the word “atypia” in its name, potentially causing concern to patients and clinicians. FEA has been associated with and may coexist with a family of indolent risk-associated proliferative lesions including atypical lobular hyperplasia (ALH), atypical ductal hyperplasia (ADH), lobular carcinoma in situ (LCIS), low-grade ductal carcinoma in situ (DCIS), and, less frequently, low-grade invasive carcinoma.…”
Section: Introductionmentioning
confidence: 99%